Dental health of pediatric patients with X-linked hypophosphatemia (XLH) after three years of burosumab therapy - Brener, Rafi; Zeitlin, Leonid; Lebenthal, Yael; Brener, Avivit (Frontiers in Endocrinology, 2022)
An inactivating PHEX gene mutation with the resultant accumulation of several mineralization-inhibiting proteins (e.g., FGF23) causes skeletal and dental morbidity in X-linked hypophosphatemia (XLH). This prospective case-control study explored the effect of burosumab, an anti-FGF23 antibody, on dental health of children with XLH. Ten children (age 4.3-15 years) with XLH underwent burosumab treatment per protocol Assessment of their dental status at treatment initiation and after 1 and 3 years of treatment included clinical, laboratory and radiographic evaluation of rickets and dentition. Orthopantomographic examinations of ten healthy sex- and age-matched controls were selected for comparison. Coronal and pulp dimensions of a selected permanent mandibular molar were measured with Planmeca Romexis® software. One year of treatment led to improvement of height z-score (p=0.019) and healing of the rickets (p<0.001) in the XLH patients, and those achievements were maintained after three years of treatment. Dental morphology of XLH patients, distinguished by increased pulp-coronal ratios compared to controls (p=0.002), remained larger after the first year of treatment (p<0.001) and did not attain the decrease expected with age after three years of treatment. Five patients had a history of recurrent dental abscesses, with three having undergone at least one episode during the year before burosumab initiation. One patient sustained recurrent abscesses throughout three years of treatment. The persistence of the unique dental morphology of XLH patients undergoing burosumab therapy, as evidenced by excessively larger pulp dimensions, supports the role of other PHEX gene-related local mineralization inhibitors, such as osteopontin, in the pathogenesis of dental morbidity.